EFFECT OF CU AND ZR ADDITION ON FE-BASED HIGH ENTROPY SUPERALLOY: A FIRST-PRINCIPLES STUDY - Fariz Aulia, Muhammad
The need for materials with high performance at high temperatures led to the development of a new class of high entropy superalloys, Superalloys which have high strength at high temperatures due to solid matrix solution strengthening ? and precipitate strengthening ?' combined with high entropy alloys having high strength and ductility at low temperatures by utilizing high entropy due to the use of five or more in large proportions. Alloy design is carried out by utilizing elements that are cheaper but still maximize performance, such as high entropy alloy based on Fe as an alternative to nickel-based superalloy. Previous research on superalloys and high entropy conventions showed the influence of Cu elements which increased the fcc phase and Zr elements which increased strength. Therefore, this study examines the effect of addition of Cu and Zr on lattice parameters and elastic properties, generalized stacking fault energy (GSFE), and Fe-based high entropy electronic alloy structures. The simulation was carried out with CASTEP based on first-principles method within the framework of functional density theory at absolute zero temperature. The calculation of the elastic properties was carried out on the fcc structure with 8 atoms with variations of Cu and Zr of 0 and 12.5 at.% using the Voigt–Reuss–Hill approximation. Geometry optimization, GSFE calculations, and electronic structure calculations were performed on an fcc structure with 24 atoms consisting of 12 layers. The GSFE is calculated by comparing perfect structure with structure containing fault. Electronic structure analysis was carried out to determine the density of states and charge density difference in the alloy. The simulation results show that increasing the concentration of Cu, adding Cu, and adding Zr by 4.17 at.% increase the lattice parameters, decrease the density of states at the Fermi Energy, and increase the accumulation of charges so that the bonds between atoms become weaker, the distance between atoms becomes more tenuous, and the ratio of stable stack fault energy to unstable stacking fault energy becomes lower. The addition of Cu will increase the stable stacking fault energy thereby increasing the ductility of the alloy, while the addition of Zr will decrease the stable stacking fault energy increasing the strength of the alloy and slightly decreasing the ductility of the alloy. This study is expected to be a guideline for further research in the development of advanced materials, especially high entropy superalloys.